Associations between the METS-IR index and cognitive function in community-dwelling Chinese middle-aged and older adult individuals: a cross-sectional study - Nian Jiang; Nian Jiang; Chenlu Ma; Chenlu Ma; Zhenning Feng; Zhenning Feng; Yongjun Tang; Yongjun Tang; Xiaolong Chen; Xiaolong Chen; Yingxu He; Yingxu He; et al. (Frontiers in Public Health, 2025)
ObjectiveThe relationship between insulin resistance and cognitive function has long been a subject of interest, but the association between the metabolic syndrome-insulin resistance (METS-IR) index and cognitive impairment remains unclear.MethodsWe utilized data from the 2015 China Health and Retirement Longitudinal Study (CHARLS) national survey, which, after screening, included a final sample of 12,307 participants. Cognitive function was assessed through face–to–face interviews via the MMSE scale. Multivariate logistic regression was used to evaluate the correlation between the METS-IR index and cognitive impairment. Using regression analysis results from fully adjusted models, we subsequently explored the nonlinear relationship between the METS-IR index and cognitive impairment via smooth curve fitting with constrained cubic splines and sought potential inflection points. Additionally, we executed a battery of sensitivity and subgroup analyses to validate the robustness of our findings.ResultsThe study included 12,307 participants, of whom 49.02% were aged 45–60 years and 52.89% were female. The results revealed that for each unit increase in the METS-IR index, the risk of cognitive impairment increased by 1.4% (OR = 1.014, 95% CI: 1.004–1.023; p < 0.01). When the METS-IR index was used as a categorical variable, compared with Q1, the odds of cognitive impairment increased by 17.1, 38.7, and 49.5% for each unit increase in the METS-IR index in the Q2, Q3, and Q4 groups, respectively. In addition, a nonlinear pattern was found in the analysis, and the endpoint of the METS-IR index was determined to be 38.1. On the left side of the endpoint, a one-unit increase in the METS-IR index was associated with a 3.1% increase in the risk of cognitive impairment. On the right side of the endpoint, the risk of cognitive impairment increased by 1.0% for each unit increase in the METS-IR index (all p < 0.05).ConclusionThis study highlighted the significant association between high METS-IR and the risk of cognitive impairment in Chinese middle-aged and older adult individuals. In addition, there was a specific nonlinear relationship between the METS-IR index and cognitive impairment (the inflection point was 38.1). Lowering the METS-IR index below 38.1 through lifestyle changes and diet control can significantly reduce the risk of cognitive impairment and may decrease the incidence of dementia.